TATA KELOLA BADAN USAHA MILIK DESA ( BUMDES) NAMBUS BESTARI DESA TANJUNG DARUL TAKZIM KECAMATAN TEBING TINGGI BARAT KABUPATEN KEPULAUAN MERANTI TAHUN 2021 - Ramadhan, Tegar zikri; ', Ishak (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
BUMDes Nambus Bestari is a BUMDes located in Tanjung Darul Takzim Village, Tebing Tinggi Barat District, Meranti Islands Regency. This BUMDes is included in the advanced BUMDes category and received an award as one of the Most Advanced BUMDes in Meranti Islands Regency in 2021. This research aims to find out how the Nambus Bestari BUMDes is managed so that it can become an advanced category and increase the village's original income. The location of this research was carried out in Tanjung Darul Takzim village. The type of research used is a qualitative method and descriptive research type with data collection techniques in the form of observation, interviews and documentation. The number of informants in this research was 9 people. The results of this research are that the governance of BUMDes Nambus Bestari applies 4 principles, namely Transparency by opening up information to the public, Accountability by reporting responsibility for each activity, Fairness which makes all BUMDes parties must make policies by consensus so as to create a sense of justice for the community and parties. BUMDes and third parties, and Responsibility for the results of BUMDes performance to the community. Keywords: Governance, BUMDes, Most Advanced